The research of glued frame-mounted wooden constructions - Muselemov K. M., Ustrakhanov O. M., Kalieva M. K., Manapov R. M. (Science in figures, 2016)
the authors of this article note that the fast pace and modern construction make qualitatively new demands on building materials and structures. While great attention is paid to the production of glued wooden structures. Such designs on a number of technical and economic indicators are superior to metal and concrete have low component weight, relatively high strength and stiffness with sufficient reliability and durability. At the same time, negative characteristics of the wood (the dependence of the properties from its structure, defects, need for and considerable expense of quality timber, excessive massiveness of the cross-sections, creep under sustained loading, etc.) restrict the scope and impair the indicators of glued wooden structures. One of the ways to address these shortcomings and increase techno-economic efficiency – reinforcement of sections of glued wooden structures and elements of steel or fiberglass reinforcement. This can significantly reduce the consumption of wood, reduce Assembly mass, to improve the quality and reliability of wooden structures, working mainly in bending and compression with bending.
Keywords: стальная арматура; жесткость; клееные деревянные конструкции; стеклопластиковая арматура; сжатие; glued wooden structures; steel rebar; fiberglass rebar; compression; hardness